A space-gamified approach to examine muscle contraction behaviour in children and adolescents with spastic cerebral palsy: feasibility, acceptability and repeatbility - Heieis, Jule; Duran, Ibrahim; Schönau, Eckhard; Fritzsche, Christoph; Götz, Bettina; Kehe, Laura; Meier, Moritz; Spiess, Karoline; Bloch, Wilhelm; Rittweger, Jörn (Frontiers in Pediatrics, 2025)
IntroductionCerebral palsy (CP) is the most common disease affecting mobility among children. However, relatively little is known about the muscle phenotype and the resulting impairments in muscle function of this population. We therefore examined feasibility and acceptability of a muscle testing protocol that is based on the muscle examinations of astronauts and in bed-rest studies in children and adolescents with CP (clinical trial registry number DRKS00031107).MethodsTwelve participants, aged between 8 and 18 years, with CP and age-matched able-bodied counterparts (Ctrl) have been included to the study. They completed testing procedures on two visits. Participants performed isometric maximum voluntary contractions, step and ramp contractions in plantarflexion on a custom build dynamometer. The tasks were visualized using a torque-controlled video game. We computed steadiness, defined as standard deviation of the fluctuations, and slope, as well as the achieved MVC. Data were statistically analyzed via Intraclass correlation coefficient (ICC) for between-visit analysis and Mann-Whitney U test for between-group analysis.ResultsOne participant of the CP group was not able to perform the tasks and dropped out for the second visit. Especially younger children and children with cognitive impairments were not able to adequately answer the acceptance questionnaire. The MVC of Ctrl was higher in both visits and was excellently repeatable. During step contractions Ctrl showed lower fluctuations in both visits. Also, during ascending ramp contractions Ctrl showed less fluctuations but only at visit 1. During descending ramp contractions steadiness was better in Ctrl at both visits. Performance parameters were all poorly repeatable, because the CP group improved their performance in all tasks at visit 2.DiscussionApplication of our gamified muscle testing protocol was well acceptable and mostly feasible. Contrasting with constant isometric contractions and decreasing ramp contractions, the performance of children with CP during ascending ramp contractions improved to the level of control subjects within 2 visits. A crucial prerequisite to perform successful measurements are good cognitive skills and at least one familiarization visit.Clinical Trial Registrationhttps://www.drks.de/DRKS00031107, identifier (DRKS00031107).